Intrauterine Growth Curves for Singleton Live Babies in Paropakar Maternity and Women’s Hospital in Nepal - Aryal, D R; Gurung, R; Misra, S; Khanal, P; Pradhan, A; Gurubacharya, S M (Journal of Nepal Health Research Council, 2012)
Background: To construct birth weight, crown heel length and head circumference centile chart referenced to gestational age for Nepalese infants. Methods: The study was conducted over a period of six months. It included consecutive live births from 28 to 42 weeks of gestation. Their birth weight, crown-heel length and head circumference were recorded. Smoothed percentile values along with curves were created using the Lambda Mu Sigma (LMS) method. The curves were compared with one of the Indian study. Results: A total of 9710 newborns were measured. The mean birth weight, crown-heel length, head circumference at 40 weeks were 3023g, 49.22cm and 33.61cm respectively. Smoothed percentile values calculated gave the cutoffs for defining small and large gestational age for Nepalese newborns. Comparison with Indian study showed significant difference (p